Español - Gagliardi, Martin (Revista Argentina de Neurocirugía, 2020)
Introduction The oblique lumbar interbody fusion (OLIF) is an alternative lumbar fusion procedure that uses the anatomical corridor between the aorta and the psoas muscle to approach the intervertebral disc. The possibility to expose the spine without the mobilization of great vessels or dissection of paraspinal muscles is a major advantage of this technique over other anterolateral fusion procedures. The aim of this study is to describe the OLIF technique in a step-by-step manner and to evaluate the short-term results and complications in a case series of patients treated with OLIF. Material and methods A retrospective analysis of clinical records of 18 patients treated with OLIF between 2018 and 2019 was performed. Cases with incomplete data and follow up shorter than 6 months were discarded. The variables studied included demographics, clinical and pathological background, surgical parameters, and operative results. The description of the surgical technique was made taking into account the experience of the surgical team and specific bibliography regarding the procedure. Results The clinical result was favorable in all cases, and only 3 patients presented minor complications. A profound description of the surgical technique was performed. Conclusion In this case series, OLIF showed to be a safe and efficient technique. However, high-quality clinical trials are needed to determine the clinical utility and complications profile of this procedure.